Characterization of bovine and canine animal model cartilage endplates and comparison to human cartilage endplate structure, matrix composition, and cell phenotype. Issue 4 (12th August 2020) - Lakstins, Katherine; Arnold, Lauren; Gunsch, Gilian; Khan, Safdar; Moore, Sarah; Purmessur, Devina
Abstract: There is a need to further explore mechanisms of cartilage endplate (CEP) degeneration, due to its role in the onset and progression of intervertebral disc degeneration and low back pain. Therefore, the goal of this study was to evaluate structure, matrix composition, and cell phenotype between the human and bovine or canine, both clinically relevant animal models currently used to study the intervertebral disc, CEP. This information may be used in addition to other relevant studies, to help determine optimal animal models for use in studying the role of the CEP in intervertebral disc degeneration and back pain. Endplate structure, matrix composition, cell morphology, and gene expression were evaluated using a picrosirius red/alcian blue and hematoxylin and eosin stain, a dimethylmethylene blue assay, and quantitative reverse transcription polymerase chain reaction. The bovine and canine CEPs were thinner with more rounded cells and thicker bony endplates. The canine CEP contained significantly more sulfated glycosaminoglycans. The bovine CEP demonstrated higher expression of ACAN, COL1, and COL2 and lower expression of T, FBLN1, and collagen X (COLX) compared to the human CEP. The canine CEP had higher COL2 and lower COL1, KRT19, MKX, FBLN1, COLX expression compared to human. These similarities and differences between human and bovine or canine CEP are important to consider when evaluating which animal model is most optimal to use in future studies, interpreting research findings using these animal models and assessing translatability to the human condition. Abstract : This article compares to structure, matrix composition and cell phenotype between the human and bovine or canine cartilage endplate. The human, bovine and canine cartilage endplates demonstrate significant differences in structure/matrix composition and gene expression compared to human which are important for researchers to take into consideration when choosing the most suitable animal model for their specific research studies and when interpreting findings from cartilage endplate studies utilizing these species.